EPIDEMIOLOGICAL INVESTIGATION OF AN OUTBREAK OF ACUTE DIARRHOEAL DISEASE IN KHERAJKHAT AREA OF LAKHIMPUR DISTRICT OF ASSAM - JITENDRA SHARMA, (International Journal of Pharma and Bio Sciences, 2014)
Diarrhoea is a symptom of infections caused by a host of bacterial, viral and parasitic organisms and most of which are spread by faeces-contaminated water. In developing countries, children under three years old experience on average three episodes of diarrhoea every year.A descriptive epidemiological investigation was carried out in kherajkhat area of Lakhimpur district of Assam during the occurrence of Acute Diarrhoeal disease (ADD) cases to find out their source of infection as well as to come across the factor responsible for ADD outbreak.3 (three) nos of rectal swab specimen were collected in the Carry Blair media for culture and sensitivity test to determine the causative agent from patients those having the complain of passage of 3 or more loose or watery stools in the past 24 hours. 5 (five) nos of water sample using aseptic measures were collected from drinking water source of patients house for H2S test and bacteriological test like Most probable number (MPN).Culture shows growth of normal Flore of gut (E.coli).H2S test for water also showed no colour change after observation. But it was suspected that other bacteria may also be present in the water sample which cannot be determined by H2S test. In MPN test result also not showed the presence of bacilli. The overall attack rate of ADD cases was 1.47%. The overall case fatality rate was 3.2%.Both the sex groups were equally affected. Median affected age is 40.5 years (ranging from 6-60 years) and high risk age group was11-20 years.The cause of the outbreak was confirmed as due to the consumption of adulterant Proshad in an occasion of Swaraswati Puja as well as the unprotected wells used by the people in that area.